Jumpstarting the Raspberry Pi Zero W : control the world around you with a $10 computer - Peck, Akkana (Maker Media, 2017)
Get up and running quickly with the new Jumpstarting ebook series from Make:. The super-small $10 Raspberry Pi Zero W includes wireless LAN and Bluetooth connectivity and is 40% faster than the original Raspberry Pi.